CONCEPTUALIZATION OF THE ROLE OF SOFT SKILLS IN THE TRANSFORMATION OF A HIGHER EDUCATION LECTURER'S PROFESSIONAL ACTIVITY - Заєць, Наталія (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2025)
The article examines the role of soft skills in the transformation of the professional activity of a modern higher education institution lecturer in the context of educational digitalization and changes in the educational paradigm. The main theoretical approaches to the conceptualization of soft skills are analyzed, and their structure and specific features in the professional activity of higher education lecturers are outlined. The relationship between the development of soft skills and the effectiveness of pedagogical activity, lecturers’ capacity for innovation, adaptability to educational changes, and the creation of a student-centered learning environment is revealed. The aim of the study is to provide a theoretical substantiation and conceptualization of the role of soft skills in the transformation of the professional activity of higher education lecturers under conditions of a shift in the paradigm of professional interaction. The objectives of the study include conducting a theoretical analysis of the essence and structure of soft skills in the context of lecturers’ professional activity; analyzing the peculiarities of the transformation of lecturers’ professional activity in response to contemporary educational challenges; and systematizing the key soft skills necessary for effective pedagogical activity in the modern educational environment. To achieve the stated objectives, the following research methods were employed: analysis of scientific literature, theoretical methods (analysis and synthesis), and pedagogical observation. The findings demonstrate that soft skills constitute an integral component of the professional competence of higher education lecturers and act as a catalyst for the transformation of pedagogical activity from a traditional knowledge-transmission model to the facilitation of learning and the personal development of higher education students.